2001
DOI: 10.1046/j.1440-1827.2001.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability of papillary subtype of human gastric adenocarcinoma and hMLH1 promoter hypermethylation in the surrounding mucosa

Abstract: Gastric cancer has striking heterogeneity in histological pattern, cellular phenotype, genotype, biomarkers, and biological behavior. We focused on the specific morphological papillary phenotype of gastric adenocarcinoma and attempted to identify its distinct molecular characteristics. In our comparative study, early stage papillary (papillary-dominant) gastric cancer showed a significantly higher and more widespread high-frequency microsatellite instability (MSI-H) than other morphological types. Analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 23 publications
(62 reference statements)
3
32
0
Order By: Relevance
“…In our present study, however, methylation of the hMLH1 promoter was detected in non-cancerous mucosa adjacent to both solitary (6 out of 12, 50%) and multiple (5 out of 8, 63%) gastric tumours with MSI-H. Similarly to our present results, Guo et al (2001) has recently reported a high frequency (40%; 4 out of 10) of hMLH1 methylation in non-cancerous mucosa adjacent to gastric cancer showing MSI-H. The exact cause of these discrepancies among reports remains uncertain.…”
Section: Molecular and Cellular Pathologysupporting
confidence: 90%
“…In our present study, however, methylation of the hMLH1 promoter was detected in non-cancerous mucosa adjacent to both solitary (6 out of 12, 50%) and multiple (5 out of 8, 63%) gastric tumours with MSI-H. Similarly to our present results, Guo et al (2001) has recently reported a high frequency (40%; 4 out of 10) of hMLH1 methylation in non-cancerous mucosa adjacent to gastric cancer showing MSI-H. The exact cause of these discrepancies among reports remains uncertain.…”
Section: Molecular and Cellular Pathologysupporting
confidence: 90%
“…Medullary-type colorectal carcinoma shows hypermethylation of the hMLH1 promoter with loss of hMLH1 expression [26]. As already mentioned, papillary adenocarcinoma of the stomach has the same features [8]. Therefore, this evidence suggests that gastrointestinal carcinomas with MSI predominantly occur at a specific site within each organ in elderly women.…”
Section: Discussionmentioning
confidence: 55%
“…More than one third of papillary and solid-type, poorly differentiated adenocarcinomas showed MSI in elderly patients with gastric carcinomas. High proportions (26-40 %) of MSI have been reported in papillary carcinoma [8,24]. Papillary or papillotubular adenocarcinoma is proposed to be a distinct morphological type with a molecular pathway of MSI because microsatellite-unstable papillary carcinoma has been found to exhibit preferential hypermethylation of the hMLH1 promoter, with absence of hMLH1 expression, and frequent mutations in genes such as BAX, TGFbRII, MSH3, and MSH6 [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr. Arai and his colleagues took advantage of a particular series of surgical cases at a single institute, which mainly treats the elderly, and they clearly characterized MSI-positive tumors, which tended to occur in older patients and exhibited a female preponderance and particular histological features. As previously reported, MSI in earlystage adenocarcinoma with papillary features (papillary subtype of well-differentiated adenocarcinoma) is often caused by MLH1 promoter methylation [5], and the concept of field cancerization arising from epigenetic changes has now been extended to and established for other cancers and genes [6]. Arai further showed that a solid subtype of poorly differentiated adenocarcinoma that usually appears as a component in a progressive stage also gains MSI during tumor growth.…”
mentioning
confidence: 75%